SAT0458 A Meta-Analysis of the Effects of Calcium Channel Blockers for the Treatment of Raynaud's Phenomenon Including Low and Higer Doses of Calcium Channel Blockers. (9th June 2015) - Rirash, F.; Pope, J.E.; Tingey, P.; Maxwell, L.; Harding, S.; Tanjong-Ghogomu, E.; Pardo, J.; Tugwell, P.; Wells, G.A.
Abstract : Background: It is known that calcium channel blockers (CCBs) can be effective in the treatment of Raynaud's Phenomenon (RP). However, the differences in treatment effect between primary (idiopathic) RP and RP secondary to a connective tissue disease are not as well described and the various doses of CCBs and their efficacy are less known. Objectives: To assess the benefits and harms of calcium channel blockers (CCBs) versus placebo for the treatment of Raynaud's phenomenon (RP) in this review. Methods: The Cochrane library (including CENTRAL), MEDLINE, EMBASE and Clinicaltrials.gov were searched up to June 2014 for randomized controlled trials (RCTs) examining RP. Outcomes of interest were: 1) Frequency of Raynaud's attacks (average/week), 2) Duration of attacks (minutes), 3) Severity of attacks (10 cm Visual analogue scale) 4) Pain, 5) Patient global, 6) Withdrawals and 7) Serious adverse events. Fixed effects models were used to calculate mean differences (MD) or standardized mean differences (SMD) for continuous outcomes and pooled risk ratios (RR) for dichotomous outcomes. Heterogeneity was determined using Chi-squared and I2tests and was considered significant if I2>50%. Subgroup analysis by disease type (primary or secondary), CCB dosage (low, medium or high) and CCB type (mainly Nifedipine and Nicardipine) were performed. Results: Of the 2337 articles, 939 participants from 36 RCTs investigating the effect of CCBs vs. placebo were included. The majority of these studies were crossover RCTs with low to moderate quality of evidence and used low dose CCBs (i.e. Nifedipine<60mg/day, Nicardipine<90mg/day). Most trials reported only some of the outcomes of interest. CCBs were significantly more effective in reducing the frequency of attacks in 22 RCTs with 978 participants [(MD -2.6295%CI -3.38, -1.88), p<0.00001] and the severity of attacks in 17 trials with 792 participants [(MD -0.73 95% CI -0.99, -0.47), p<0.00001].There were no statistically significant differences in duration, pain or withdrawals due to adverse events between CCBs and placebo. Patient global was only reported in one study and serious adverse events were not reported. The presence of significant heterogeneity was addressed by sensitivity and subgroup analyses. Overall, CCBs reduced the frequency and severity of attacks irrespective of dosage, particularly for primary RP. Low dose CCBs reduced the frequency of attacks by 3.3 per week vs. medium dose at 5.6. CCBs reduced frequency of attacks (per week) in primary RP by 3.9 vs. 0.5 in secondary RP. Similar trends were seen in severity of attacks for low dose vs. medium dose CCBs and primary vs. secondary RP. Limitations were identified such as cross over studies with possible carryover effects, low trial quality, missing outcomes of interest and heterogeneity of trials. Conclusions: CCBs are effective in managing RP, particularly primary RP. The effect may be blunted in secondary RP. Low dose CCBs are not as effective as higher dosing. Disclosure of Interest: None declared